Impaired modulation of the trigeminal caudal nucleus by the locus coeruleus in diabetic mice: the role of GABAergic and glycinergic neurons - Alberto Mesa-Lombardo; Nuria García-Magro; Angel Nuñez; Yasmina B. Martin (Frontiers in Neuroanatomy)
The trigeminal system plays a crucial role in processing somatosensory information, and its modulation is essential for maintaining sensory homeostasis. This study investigates the inhibitory modulation of trigeminal somatosensory responses by the locus coeruleus (LC), which is involved in numerous cognitive and physiological functions. Previous electrophysiological investigations have shown a diminished ability of the LC to inhibit somatosensory responses in the caudalis division of the spinal trigeminal nucleus (Sp5C) in diabetic mice. We hypothesize that γ-Amino-butyric acid (GABA)ergic and glycinergic neurons in the Sp5C may also participate in modulatory action from the LC. Using unit recordings in isoflurane anesthetized control and streptozotocin-induced diabetic mice, we examined the effect of LC electrical stimulation on GABAergic and glycinergic neurons, while monitoring trigeminal somatosensory responses to vibrissal stimulation. Local applications of bicuculline or strychnine (antagonists of GABAergic and glycinergic receptors, respectively) demonstrated that GABAergic and glycinergic neurons are under the control of noradrenergic projections from the LC by activation of α1 and α2 noradrenergic receptors, respectively. In diabetic mice, the functionality of these inhibitory circuits was reduced, contributing to the observed deficiency in LC-mediated sensory modulation and likely contributing to generation of neuropathic pain. Immunohistochemical experiments confirmed the presence of α1 and α2 noradrenergic receptors in GABAergic and glycinergic neurons that were altered in diabetic mice. In conclusion, the LC modulation exerted on the somatosensory responses in the Sp5C is not only through noradrenergic receptors on glutamatergic projection neurons but also exerts its control through projections to inhibitory interneurons.